Acute exposure of di(2-ethylhexyl) phthalate (DEHP) induces immune signal regulation and ferroptosis in oryzias melastigma. (February 2021) - Yin, Xiaohan; Zeb, Rabia; Wei, Hui; Cai, Ling
Abstract: The plasticizer di (2-ethylhexyl) phthalate (DEHP) is becoming increasingly abundant throughout the global environment as plastic pollution becomes highly severe, especially in the ocean. The adverse effects of DEHP have garnered increasing concern as they are recognized as endocrine disruptors. However, information on the effects of DEHP in marine organisms remains limited. In this study, acute toxic effects on marine medaka ( Oryzias melastigma ) following DEHP exposure were investigated. Transcriptome analysis was performed on the livers of medaka exposed to DEHP for 6 and 24 h. Results showed that 1595 genes were affected in all the analyzed specimens, and several genes expressed variably according to sex. Some pathways associated with immunity, metabolism, and endocrine system were significantly enriched, with the complement system appearing to be the most affected immune pathway. Pathway enrichment indicated that, under acute DEHP exposure, the immune response of females tended to be more sensitive than that of males. In addition, ferroptosis occurred in response to DEHP exposure, which resulted in an enrichment of the ferroptosis pathway along with iron overload, an increase in malondialdehyde (MDA) and lipid peroxidation (LPO) content, and a decrease in glutathione (GSH) levels. These results indicate that a form of cell death characterized by iron-dependence occurred following DEHP exposure, but the underlying mechanism requires further analysis. This study implies that DEHP can alter some molecular regulation patterns within a short period and induce cell death through ferroptosis. Graphical abstract: Image 1 Highlights: DEHP induced the enrichment of immune, metabolism pathways in marine medaka. Complement system appeared to be the most affected immune pathway in marine medaka. Female immune response seemed to be more sensitive than males under DEHP exposure. Ferroptosis occurred in marine medaka following DEHP exposure.